Pemahaman Bid’ah Menurut Ulama di Desa Teluk Pulai Dalam Kecamatan Kualuh Leidong - Safrida Fitri Nasution (Medan Resource Center, 2021)
The discussion about bid'ah is quite an interesting conversation, bid'ah is not a new vocabulary in the midst of the Islamic ummah. From the first heresy has always been interesting to write about. Even the scholars have discussed all aspects of the heresy. But even so, it still reaps conflict in the current era of the Islamic ummah. Because this problem is sometimes very confusing. In Islamic society, especially in Indonesia, there are different understandings of heresy. Some think that not all bid'ah is misguided. While a small number of people think that all bid'ah is heretical. Studying the problem of bid'ah in Islamic society is not easy, because it requires a definition that develops and arises around the use of the word